Interferon‐γ release assays in the diagnosis of active tuberculosis disease in a low‐incident setting: a 5‐year review of data. (11th February 2013) - Lavender, T. W.; Barrett, A.; Magee, J.; Ong, E. L. C.; Drancourt, M.
Abstract The role of interferon‐γ release assays in the diagnosis of active tuberculosis disease is uncertain, and recent guidelines do not support their routine use. We reviewed the clinical records of 415 patients who had a QuantiFERON‐TB Gold In‐Tube assay between 29 June 2005 and 28 October 2010 to determine its performance in the diagnosis of active tuberculosis disease in a low prevalence setting, specifically in human immunodeficiency virus (HIV) ‐positive and HIV‐negative patients, those of UK and non‐UK origin, and those with pulmonary and extrapulmonary disease. For the diagnosis of active tuberculosis disease the overall sensitivity of QuantiFERON‐TB Gold In‐Tube assay was 71.4% (95% CI 59.3–81.1), specificity was 81.0% (95% CI 75.5–85.6) and negative predictive value was 92.6% (95% CI 88.2–95.5). No significant difference in sensitivity was seen in culture‐positive and culture‐negative tuberculosis, in pulmonary and extrapulmonary disease, or with HIV infection. Specificity and negative predictive value were significantly higher in patients of UK origin compared with those of non‐UK origin (89.3% (95% CI 83.3–93.3) and 97.1% (95% CI 92.7–98.9) versus 66.3% (95% CI 55.6–75.5) and 83.3% (95% CI 72.6–90.4)). Our study suggests that there may be a role for interferon‐γ release assays in excluding active tuberculosis disease, particularly extrapulmonary disease, in patients originating from areas of low tuberculosis incidence, with a negative test highly predictive of a lack of active tuberculosis disease in this group. We cannot support the use of these assays in the diagnosis of active tuberculosis infection in patients from areas of higher incidence.